Establishing the conditions for the formation of a near-wall layer of solid granular fill of a rotating drum - Naumenko, Yuriy; Deineka, Kateryna; Myronenko, Tamara (Eastern-European Journal of Enterprise Technologies, 2021)
This paper reports the assessment of the influence of dynamic motion parameters on the formation and disappearance at the cylindrical surface of the chamber of the rotating drum of the near-wall layer of non-loose granular fill. Based on the results of experimental visualization of the flow, the effect of solidity on the behavior of granular fill was revealed. The hydrodynamic effect of fill quasi-liquefaction under the action of solidity has been established, which involves the occurrence of a connecting interaction between adjacent layers and the surface of the chamber. Conversion of shear circulation flow to homogeneous dense clustered stream with slipping and rolling without relative movement of particles was detected. The hydrodynamic characteristics of circulation flow transition to the near-wall layer mode during rotation acceleration have been defined. Such a transition is implemented by smoothly increasing the thickness of the layer when the rest of the fill is circulated at the bottom of the chamber. The effect of the rheological hysteresis of the movement of the rotating chamber fill, caused by quasi-liquefaction of non-loose granular environment, has been established. The effect implies exceeding the speed limit ωfl in the formation of a near-wall layer, at rotation acceleration, above the boundary ωdl of the layer disappearance when the rotation slows down. The manifestation of hysteresis mainly increases with an increase in Reynolds number. The intensity of increased hysteresis manifestation increases with a decrease in the degree of filling the chamber. The value of the Froud number for the ωfl and ωdl boundaries increases with the increase in Re. It has been established that at the relative particle size of the dispersed fill ψdc≈(0.065–1.04)·10‑3 and Re=30–500, Fr=1–2.9, for the ωfl boundary, and Fr=0.5–1.4, for the ωdl boundary. The Fr value for the ωfl limit was found to exceed this value for the ωdl boundary by 1.6–2.1 times. The established effects make it possible to substantiate the rational parameters for the grinding process in drum-roll mills